Frequency-Selective Surface Stopband Designed with a Genetic Algorithm for Gain Enhancement of a Broadband Monopole Antenna - Nguyen, DucDung; Seo, Chulhun (Journal of Electromagnetic Engineering and Science, 2022)
This paper presents an unusual, high-performance, cost-efficient, wideband frequency-selective surface (FSS) designed with a genetic algorithm (GA) and its effect on the performance of a broadband M-shaped monopole antenna. Each FSS unit cell with the dimensions of 0.2λ0 × 0.2λ0 × 0.01λ0 acts as a stopband filter for a wide bandwidth of 5.5 GHz (105%, 2.6–8.1 GHz). The FSS properties and advantages to antennas were tested via numerical simulations and measurements, respectively. Using the 6×6 array of the designed FSS unit cell as a reflector, the antenna impedance bandwidth improved from 96.1% (3.1–8.1 GHz) to 98.07% (3.3–8.4 GHz), with a center frequency of 5.2 GHz. In addition, the antenna gain improved at the maximum of 7.8 dBi, which was sustained from 9 dBi to 10.1 dBi for the entire bandwidth.